2012
DOI: 10.1093/europace/eur419
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop cardiac pacing vs. conventional dual-chamber pacing with specialized sensing and pacing algorithms for syncope prevention in patients with refractory vasovagal syncope: results of a long-term follow-up

Abstract: The results of this retrospective analysis show that, in order to prevent a recurrence of VVS in patients with a cardioinhibitory response to HUTT, dual-chamber CLS pacing was more effective than dual-chamber pacing with conventional algorithms for syncope prevention in preventing bradycardia-related syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 26 publications
1
22
0
3
Order By: Relevance
“…Bortnik et al 21 in a long-term follow-up study including 35 patients studied the role of CLS pacing in preventing syncopal events recurrence. Palmisano et al 22 in a retrospective observational long-term follow-up study showed that the syncopal recurrence was 4% in dual-chamber CLS pacemaker group (n: 25) and 38% in patients (n: 16) who received a conventional pacing dual-chamber pacemaker; there was no statistically significant difference (8% vs 10%, p = 0.876) in presyncopal symptoms between the two groups among patients without syncopal recurrences.…”
Section: Discussionmentioning
confidence: 97%
“…Bortnik et al 21 in a long-term follow-up study including 35 patients studied the role of CLS pacing in preventing syncopal events recurrence. Palmisano et al 22 in a retrospective observational long-term follow-up study showed that the syncopal recurrence was 4% in dual-chamber CLS pacemaker group (n: 25) and 38% in patients (n: 16) who received a conventional pacing dual-chamber pacemaker; there was no statistically significant difference (8% vs 10%, p = 0.876) in presyncopal symptoms between the two groups among patients without syncopal recurrences.…”
Section: Discussionmentioning
confidence: 97%
“…Although no prospective randomized clinical trials exist to determine which pacing feature is superior, several recent nonrandomized or retrospective trials suggest that close look stimulation may be preferable. 94,95 Further research is needed in this evolving approach to management of NCS.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…De estos, 25 pacientes recibieron un marcapasos con sistema CLS y 16 un algoritmo convencional para prevención de síncope. Durante el seguimiento un paciente (1%) del grupo con marcapasos con CLS y 6 (36%) del grupo de marcapasos convencional (p = 0,01) desarrollaron síncope 34 .…”
Section: Estimulación Convencional Frente a Sistema De Asa Cerradaunclassified